PENGATURAN DAN PENGURUSAN PEMBANGUNAN MENARA TELEKOMUNIKASI/BTS (BASE TRANSCEIVER STATION) DI KOTA BONTANG - Romadhoni, Kurnia (Jurnal Administrasi Publik, 2016)
Abstract: Managements and Adjustments of Telecommunication Tower/BTS (Base Transceiver Station) Developments in Bontang City The implementation of national development is an act that has been frequently done in Indonesia. Build upon Number 23 Year 2014 constitution about the local governments announcing that local governments are now authorized to manage and arrange their own governmental needs and local community interest on their own region, adapted with the national development purpose that could not be possibly implemented by the central government. Telecommunication tower has been functioned as the main supportive infrastructure in the world of technological information and communication. The establishment of the communication tower or also called BTS (Base Transceiver Station) was rapidly evolved in Bontang City. Issues that connected with construction of the BTS tower should be firmly addressed by the city government as an institution that authorized enough in supervision and the adjustment of the development. Overall, the management and adjustments of the development of telecommunication towers/BTS (Base Transceiver Station) in Bontang City was finely implemented, however, in the progress of implementation and the management itself, a lot of things was still considered minus. Such circumstances caused by the lack of socialization about the Bontang City Constitution Number 14 Year 2006 about the Management of Cellular Communication Tower Development causing a frequent condition of misunderstanding among departments who manages the developing license of the cellular tower in Bontang City. Keywords: Managements and Adjustments BTS (Base Transceiver Station), Intrastructur, local goverment, Bontang City. Abtrak : Pengaturan Dan Pengurusan Pembangunan Menara Telekomunikasi/ Bts (Base Transceiver Station) Di Kota Bontang Pelaksanaan pembangunan nasional merupakan suatu kegiatan yang sedang giat dilakukan di Indonesia. Berdasarkan Undang-undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah, pemerintah daerah kini memiliki wewenang untuk mengatur dan mengurus sendiri urusan pemerintahan dan kepentingan masyarakat setempat di daerahnya sesuai dengan tujuan pembangunan nasional yang tidak mungkin dapat dilaksanakan sendiri oleh pemerintah pusat. Menara telekomunikasi sebagai infrastruktur pendukung yang utama dalam dunia teknologi informasi dan komunikasi. Pendirian bangunan menara telekomunikasi atau BTS (Base Transceiver Station) di Kota Bontang berkembang dengan sangat pesat. Permasalahan yang terkait dengan pembangunan menara BTS tersebut harus disikapi secara tegas oleh pemerintah kota sebagai institusi yang cukup berwenang dalam pengaturan dan pengurusan pembangunan dari menara-menara BTS yang sudah terbangun maupun yang sedang dalam perencanaan untuk dibangun. Pengaturan dan pengurusan pembangunan menara telekomunikasi/BTS (Base Transceiver Stasion) di Kota Bontang secara keseluruhan sebenarnya sudah sangat baik namun dalam pelaksanaannya atau pengurusannya masih banyak hal-hal yang kurang. Hal ini dikarenakan kurang adanya sosialisasi mengenai Perwali Bontang Nomor 14 Tahun 2006 tentang Penataan Pembangunan Menara Telekomunikasi Seluler sehingga masih sering terjadi salah pemahaman antara dinas-dinas terkait yang mengurusi perijinan pembangunan menara seluler di Kota Bontang. Kata Kunci : Pengaturan dan Pengurusan BTS (Base Transceiver Station), infrastruktur, pemerintah daerah, kota bontang.